Arsenic and skin cancer in the USA: the current evidence regarding arsenic‐contaminated drinking water. (5th October 2016) - Mayer, Jonathan E.; Goldman, Rose H.
Abstract: Background: Studies carried out in developing countries, such as Bangladesh and Taiwan, have reported an association between exposure to arsenic in drinking water and increased rates of non‐melanoma skin cancer. However, it is unclear whether this correlation can be extended to the populations of developed countries such as the USA, which have lower levels of arsenic exposure and differ in other factors, such as genetics, nutrition, sun exposure, and socioeconomic status. Objectives: This report examines the current evidence in an attempt to resolve whether populations in the USA have rates of skin cancer that correlate with higher arsenic concentrations. Methods: A systematic literature search was conducted using the PubMed, EMBASE, CINAHL, and Cochrane databases. Results: Six key studies were found and reviewed. Several studies conducted in US populations indicate an association between arsenic‐contaminated water and skin cancer, which may in some cases occur at arsenic concentrations of <10 μg/l, the 2001 Environmental Protection Agency (EPA) maximum allowable concentration for municipal water. Conclusions: Private wells are not regulated by the EPA's rule, and many have concentrations above the EPA maximum. In order to help curb the rising incidence of skin cancer, arsenic contamination of water warrants the attention of policymakers. Greater testing of well water and increased education and skin cancer surveillance by dermatologists in arsenic‐endemic areas may help to reduce exposure to arsenic and facilitate the early recognition of skin cancer.